Changes in functional connectivity among vestibulo-visuo-somatosensory and spatial cognitive cortical areas in persistent postural-perceptual dizziness: resting-state fMRI studies before and after visual stimulation - Yagi, Chihiro; Morita, Yuka; Yamagishi, Tatsuya; Ohshima, Shinsuke; Izumi, Shuji; Takahashi, Kuniyuki; Watanabe, Masaki; Itoh, Kosuke; Suzuki, Yuji; Igarashi, Hironaka; Horii, Arata (Frontiers in Neurology, 2023)
Introduction Persistent postural-perceptual dizziness (PPPD) is a functional chronic vestibular syndrome with symptom exacerbation by upright posture, motion, and complex visual stimuli. Among these exacerbating factors, visual exacerbation is the most specific characteristic of PPPD requiring further investigation. We hypothesized that stimulus-induced changes occur in the functional connectivity (FC) rather than simple neural activation that is involved in visual stimulation. The present study aimed to identify the neural basis of PPPD by investigating FC before and after visual stimulation. Methods Eleven patients with PPPD and 11 age- and sex-matched healthy controls (HCs) underwent resting-state fMRI (rs-fMRI) before and after task-based fMRI with visual stimuli. Results At pre-stimulus, FC between the vestibular cortex and visual areas was low, while that between the somatosensory and visual areas was high in PPPD compared with that in HCs. FC between the visuospatial (parahippocampal gyrus) and spatial cognitive areas (inferior parietal lobule) was elevated in PPPD even in the pre-stimulus condition, which no longer increased at post-stimulus as observed in HCs. In the post-stimulus condition, FC between the visual and spatial cognitive areas and that between the visual and prefrontal areas increased compared with that in the pre-stimulus condition in PPPD. Task-based fMRI demonstrated that no brain regions showed different activities between the HC and PPPD groups during visual stimulation. Discussion In PPPD, vestibular inputs may not be fully utilized in the vestibulo-visuo-somatosensory network. Given that the FC between visuospatial and spatial cognitive areas increased even in HCs after visual stimuli, elevated status of this FC in combination with the high FC between the somatosensory and visual areas would be involved in the visual exacerbation in PPPD. An increase in FC from the visual areas to spatial cognitive and prefrontal areas after visual stimuli may account for the prolonged symptoms after visual exacerbation and anxious status in PPPD.